William Marsden and John Crawfurd: English translations of Pantun in nineteenth century grammar texts - Shunmugam, Krishnavanie; Soh, Bee Kwee (Journal of Modern Languages, 2017)
The pantun, a classical verse form which began as an oral tradition, is part of the cultural heritage of the Malay people. The earliest known Malay pantun translations into English in print have been identified in approximately seven different types of text written by British colonialists in nineteenth century Malaya. These texts include two grammar references, a statistical record, three historical narratives and a collection of personal letters. This paper focuses on pantun translations into English in the two well-known Malay grammar texts of the time which were produced by William Marsden and John Crawfurd. A descriptive analysis of Marsden’s and Crawfurd’s translation styles on a selection of pantun alongside the translational considerations which had influenced their translation style will form the main discussion of this paper. A case of present-day criticism levelled at Marsden’s translation of a particularly well-known linked pantun is also reviewed here against a number of seminal translation views put forth by proponents of functionalism in translation like Christianne Nord, Julianne House and Christina Schaffner. This paper is useful as it contributes historical information on some of the earliest English pantun translations in print and highlights some of the translation issues that encompassed these nineteenth century pantun translations.